2001
DOI: 10.1037/0893-164x.15.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking in Chinese, Korean, and White college students: Genetic and ethnic group differences.

Abstract: Studies of Asian college students have found that rates of binge drinking are associated with variation in the aldehyde dehydrogenase (ALDH2) gene. Chinese and Koreans have different prevalence rates of the ALDH2*2 allele, alcohol use, and alcoholism. The association of ALDH2 status and ethnic group with binge drinking was examined in 328 Chinese, Korean, and White college students. Ethnic group differences were found, with Whites having the highest rate of binge drinking, followed by Koreans and then Chinese.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
62
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 16 publications
7
62
3
Order By: Relevance
“…Familial studies of Asian populations in Hawaii (Johnson et al, 1987 have indicated that cultural factors are more strongly associated with drinking than self-reported alcohol-induced flushing, suggesting that genetic influences on alcohol use in these groups are negligible relative to sociocultural determinants . However, these studies assessed neither ALDH2 genotype nor relationships between physiological response to alcohol and heavy drinking behavior, which has been linked to ALDH2 status in several reports (Luczak et al, 2001;Takeshita and Morimoto, 1999;Wall et al, 2001). Studies examining both ALDH2 status and cultural variables (i.e., acculturation) in relation to heavy drinking could help to clarify the relative influence of physiological and sociocultural determinants of alcohol use.…”
Section: Conclusion-resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Familial studies of Asian populations in Hawaii (Johnson et al, 1987 have indicated that cultural factors are more strongly associated with drinking than self-reported alcohol-induced flushing, suggesting that genetic influences on alcohol use in these groups are negligible relative to sociocultural determinants . However, these studies assessed neither ALDH2 genotype nor relationships between physiological response to alcohol and heavy drinking behavior, which has been linked to ALDH2 status in several reports (Luczak et al, 2001;Takeshita and Morimoto, 1999;Wall et al, 2001). Studies examining both ALDH2 status and cultural variables (i.e., acculturation) in relation to heavy drinking could help to clarify the relative influence of physiological and sociocultural determinants of alcohol use.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…Compared with individuals without an ALDH2*2 allele, those possessing one or two copies demonstrate stronger physiological reactions to alcohol ingestion (Peng et al, 1999;Wall et al, 1992Wall et al, , 1994Wall et al, , 1996. Accordingly, presence of an ALDH2*2 allele has been associated with decreased rates of alcohol use (Sun et al, 2002;Wall et al, 2001), heavy episodic (binge) drinking (Luczak et al, 2001;Takeshita and Morimoto, 1999;Wall et al, 2001) and alcohol dependence Luczak et al, 2004;Thomasson et al, 1991).…”
Section: Conclusion-resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Asian Americans typically report lower levels of alcohol consumption than Caucasians (Akutsu, Sue, Zane, & Nakamura, 1989;Luczak, Wall, Shea, Byun, & Carr, 2001;Sakai, Ho, Shore, Risk, & Price, 2005;Zane & Kim, 1994), HED still occurs (Iwamoto, Takamatsu, & Castellanos, 2012;Lee, Han, & Gfroerer, 2013). Asian Americans are typically viewed as the "model minority" and as such, drinking issues may be wrongfully ignored (Yun & Park, 2008).…”
mentioning
confidence: 99%